Lipid Synthesis in Protozoan Parasites: a Comparison Between Kinetoplastids and Apicomplexans - Ramakrishnan, Srinivasan (2013)
Lipid metabolism is of crucial importance for pathogens. Lipids serve as cellular building blocks, signalling molecules, energy stores, posttranslational modifiers, and pathogenesis factors. Parasites rely on a complex system of uptake and synthesis mechanisms to satisfy their lipid needs. The parameters of this system change dramatically as the parasite transits through the various stages of its life cycle. Here we discuss the tremendous recent advances that have been made in the understanding of the synthesis and uptake pathways for fatty acids and phospholipids in apicomplexan and kinetoplastid parasites, including Plasmodium, Toxoplasma, Cryptosporidium, Trypanosoma and Leishmania. Lipid synthesis differs in significant ways between parasites from both phyla and the human host. Parasites have acquired novel pathways through endosymbiosis, as in the case of the apicoplast, have dramatically reshaped substrate and product profiles, and have evolved specialized lipids to interact with or manipulate the host. These differences potentially provide opportunities for drug development. We outline the lipid pathways for key species in detail as they progress through the developmental cycle and highlight those that are of particular importance to the biology of the pathogens and/or are the most promising targets for parasite-specific treatment.